!Tention: A Story of Boy-Life during the Peninsular War - Fenn, George Manville, 1831-1909; Sheldon, Charles Mills, 1866-1928 (Salt Lake City, UT : Project Gutenberg, 2007)
"!Tention: A Story of Boy-Life during the Peninsular War" by George Manville Fenn is a historical novel written in the late 19th century. The story primarily revolves around two young soldiers, Private Penton Gray and the bugler Punch, as they navigate the dangers and challenges of the Peninsular War in Spain. Their journey through injury and adventure highlights themes of friendship, bravery, and the harsh realities of war from a youthful perspective. The opening of the novel captures a dramatic scene during a military engagement. Private Pen finds himself injured alongside Punch, who is also hurt but determined to reunite with their regiment. As they attempt to recover and evade enemy forces, the boys face numerous adventures, including encounters with formidable enemies and allies, such as a deposed Spanish King. Their bond and determination to survive become central to the narrative, setting a tone that balances the realities of wartime with the innocence of youth, making the story both poignant and engaging. (This is an automatically generated summary.)
Release date is 2007-05-08
Produced by Nick Hodson of London, England
Keywords: Peninsular War, 1807-1814 -- Juvenile fiction